Rancangan Inovasi Layanan Kesehatan Gigi dan Mulut: Integrasi Sistem Berbasis Web dengan Telemedicine untuk Meningkatkan Aksesibilitas - Sadikin, Muhammad; Syamanta, Arbana; Dwiki Putri, Dini Ridha; Dewi, Rofiqoh; Setiawan, Adil (LPPM Universitas Potensi Utama, 2024)
Oral health is an important component of general health that is often neglected in society. In Indonesia, many individuals experience oral health problems due to lack of access to quality health services. This is especially true in underserved areas, where people face various obstacles, such as distance, cost, and lack of information about available health services. In this PkM, researchers studied the development and implementation of a web-based oral health service system with telemedicine support to improve the accessibility and effectiveness of dental health services. Through user needs analysis and evaluation of the system prototype, the results showed that this platform allows patients to register, schedule consultations, and access dental health information online with a high level of satisfaction. Online consultations proved effective in providing accurate diagnoses, while the educational materials provided contributed to increased awareness of dental health. The results of this PkM confirm that the implementation of telemedicine in dental health services not only improves accessibility but also the quality of services, and contributes to the development of digital health systems in the future